Intratumoral injection and retention hold promise to improve cytokine therapies for cancer - Sauer, Karsten; Rakhra, Kavya; Wu, Kaida; Mehta, Naveen K.; Michaelson, Jennifer S.; Baeuerle, Patrick A. (Frontiers in Oncology, 2024)
As powerful activators of the immune system, cytokines have been extensively explored for treating various cancers. But despite encouraging advances and some drug approvals, the broad adoption of cytokine therapies in the clinic has been limited by low response rates and sometimes severe toxicities. This in part reflects an inefficient biodistribution to tumors or a pleiotropic action on bystander cells and tissues. Here, we first review these issues and then argue for the intratumoral delivery of engineered cytokine fusion proteins that have been optimized for tumor retention as a potential solution to overcome these limitations and realize the potential of cytokines as highly effective therapeutics for cancer.